STRATEGI POLITIK PASANGAN AMRIS DAN SAKTI MERAIH DUKUNGAN MASYARAKAT PADA PILKADA DUMAI TAHUN 2015 - Setiawan, Redho; ", Adli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Through the local elections allow the accommodation of the wishes and aspirations of society to realize a better life. The Constitutional Court passed a decision independent candidates provide new hope for the emergence of candidates for regional head / deputy head of the region that is relatively more open to anyone who has an interest to nominate themselves. The presence of independent candidates (Amris, SY and Sakti) will have a positive impact teradap political competition in the post of Mayor and Deputy Mayor of the period 2016-2021. The new independent candidates appeared first in Kota Dumai so seem less popular in the public eye. Independent candidates have no ideology and no mass base is strong because it is not supported by the political parties, so that it can be seen that the candidate of the independent who dare to appear, especially in the General Election Dumai should be more widely supported on several factors such as having a strong image and supported from economic factors ,Researchers detailing the following research problem: How can a political strategy and a pair Amris Way in winning support in the elections Dumai 2015?.This study used descriptive qualitative method. Data analysis using descriptive technique in which data has been collected subsequent grouped by types and their uses. Then the data is processed and analyzed according to the theory used and presented in the form of descriptions. Analysis of data is divided into two: the analysis of statistical data and non-statistical data analysis, given the data writing is not the form but the results of the analysis process used is non-statistical data analysis.Based on studies it appears that the vote is a pair Amris independent partner and Sakti gain support as many as 20 882 voice or the voice of 17.88%. If seen from the number of ballot upon verification of prospective follow Regional Head and the vote at the election Dumai 2015 elections on an independent partner of this decline amounted to 1,581 voice sounds. The decline was caused including the votes by the following: a) The pair candidate for mayor who had served became Mayor and Deputy Mayor of so many people who know the couple's lunge. b) an independent pair is not supported by sufficient funding so that the approach taken to the people not to touch the whole society.Keywords: Strategy, politics, society, independent candidate